Enoch and the Mosaic Torah: the evidence of jubilees - Boccaccini, Gabriele; Ibba, Giovanni; Ehrenkrook, Jason von; Waddell, James Alan; Zurawski, Jason (Eerdmans, 2009)
Preface: The enigma of Jubilees and the lesson of the Enoch Seminar / Gabriele Boccaccini -- Jubilees and its literary context -- The manuscript tradition of Jubilees / James C. VanderKam -- The composition of Jubilees / Michael Segal -- The relationship between Jubilees and the early enochic books (astronomical book and book of the watchers) / John S. Bergsma -- Daniel and Jubilees / Matthias Henze -- The chronologies of the Apocalypse of weeks and the book of Jubilees / James M. Scott -- The Aramaic Levi document, the genesis Apocryphon, and Jubilees : a study of shared traditions / Esther Eshel -- The book of Jubilees and the Temple Scroll / Lawrence H. Schiffman -- Jubilees, Sirach, and sapiential tradition / Benjamin G. Wright III -- The heavenly counterpart of Moses in the book of Jubilees / Andrei A. Orlov -- Jubilees and the Aamaritan tradition / Lester L. Grabbe -- The melting of mosaic and enochic traditions -- Enochic Judaism : a Judaism without the Torah and the temple / Helge S. Kvanvig -- The concept of covenant in Jubilees / William K. Gilders -- From a movement of dissent to a distinct form of Judaism : the heavenly tablets in Jubilees as the foundation of a competing Halakah / Gabriele Boccaccini -- Abram's prayer : the coherence of the pericopes in Jubilees 12:16-27 / Jacques van Ruiten -- Reconsidering Jubilees : prophecy and exemplarity / Hindy Najman -- Jubilees between Enoch and Qumran -- 4Q265 and the authoritative status of Jubilees at Qumran / Aharon Shemesh -- Purity and impurity in the book of Jubilees / Lutz Doering -- Tradition and innovation in the calendar of Jubilees / Jonathan Ben-Dov -- The book of Jubilees and the origin of evil / Loren T. Stuckenbruck -- The festivals of Pesaf and massot in the book of Jubilees / Betsy Halpern-Amaru -- Eschatological impulses in Jubilees / John C. Endres -- Amplified roles, idealized depictions : women in the book of Jubilees / Kelley Coblentz Bautch -- Enochic and mosaic traditions in Jubilees : the evidence of angelology and demonology / Annette Yoshiko Reed -- Worship in Jubilees and Enoch / Erik Larson -- The book of Jubilees and early Jewish mysticism / Martha Himmelfarb -- Where does Jubilees belong? -- Jubilees, the temple, and the Aaronite priesthood / David W. Suter -- Jubilees and enochic Judaism / David R. Jackson -- Jubilees, Qumran, and the Essenes / Eyal Regev -- The book of Jubilees : a bibliography, 1850-present / Veronika Bachmann and Isaac W. Oliver